The human person and the post-human vision: A theological approach - Douramani, Georgia (Bioethica, 2024)
Arriving in the era of Second - or Liquid - Modernity, man succeeds in breaking the shackles of tradition, and relying on his own forces promotes the model of the free, self-sufficient man. The desire of man to evolve into a more gifted being in order to improve his conditions of life is not new, but inherent in mankind. Philosophy and religion tried to provide solutions to the ardent demand of improving human nature, each one from its own perspective. In the era of Late (Liquid) Modernity, man has managed to break the limitations of tradition and, based on his own resources, to promote the model of the free man who voluntarily determines his own destiny. In our time through the extremely rapid progress of Science and Technology, man redefines his identity as a human person and his overall relationship with God and the environment as well. The holistic transformation of the structure elements that formed the foundations of modernity is typical of the transition to a post-modern era that requires a new identity for man, that of the post-human. The post-human is no longer an utopian vision but is sought through Transhumanism and interfaces. The question is whether mankind will preserve its identity as a “human person” with the characteristics of the being created by God or whether it will be transformed into a narcissistic, omnipotent and autonomous existence, separating mankind from its humanity.